PHENOMENA AND IMPLICATIONS OF FINANCIAL TECHNOLOGY (FINTECH) ADOPTION IN THE FINANCIAL & BANKING INDUSTRY SECTOR IN GLOBAL, REGIONAL AND INDONESIAN CONTEXT - Fuadi; Munawar Rizki Jailani; Hafas Furqani; Baihaqi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Abstract